2021
DOI: 10.14309/ajg.0000000000001619
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Initial Humoral Immune Response to SARS-CoV-2 Vaccines Among Patients With Inflammatory Bowel Diseases

Abstract: INTRODUCTION:Although an additional coronavirus disease 2019 vaccine dose for immunocompromised persons has been recommended in some countries, further data to guide vaccination strategies for patients with inflammatory bowel disease (IBD) are urgently needed. We sought to identify factors affecting initial humoral immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines among patients with IBD.METHODS:In this prospective cohort of SARS-CoV-2 immunized patients with IBD, we eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 28 publications
4
33
0
Order By: Relevance
“…Such a difference may be due to the older age of the HC group, mainly composed of healthcare workers, considering the previously demonstrated influence of age on SARS-CoV-2 vaccination response and long-term memory maintenance [ 36 ]. The independent impact of age on immunogenicity was also confirmed in multiple adult IBD cohorts [ 15 , 17 ] and by our group in another cohort of immune-compromised children [ 37 ].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Such a difference may be due to the older age of the HC group, mainly composed of healthcare workers, considering the previously demonstrated influence of age on SARS-CoV-2 vaccination response and long-term memory maintenance [ 36 ]. The independent impact of age on immunogenicity was also confirmed in multiple adult IBD cohorts [ 15 , 17 ] and by our group in another cohort of immune-compromised children [ 37 ].…”
Section: Discussionsupporting
confidence: 71%
“…In the present study, we further explored the impact of specific immune-suppressive regimens on the immunogenicity of BNT162B2 in pIBD. A suboptimal response in adult IBD on therapy with anti-TNFα in comparison with either IBD treated with other immune-suppressive regimens or HC was recently published [ 13 , 14 , 15 , 16 , 17 , 18 ]. For the first time in the pediatric context, we confirmed such findings, showing that pIBD on therapy with anti-TNFα (Infliximab or Adalimumab) developed a lower response in terms of Anti-S ab compared to patients receiving Azathioprine or Mesalazine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2-5) Those who were less likely to seroconvert were older in age, received the BNT162b2 vaccine, and be on combination therapy with an anti-tumor necrosis factor alpha (TNF)-alpha inhibitor and an immunomodulator. (3)(4)(5) The "HumoRal and CellULar initial and Sustained immunogenicity in patients with IBD" (HERCULES) study found that after vaccination for COVID-19, antibody concentrations were lower in patients with IBD than in healthy controls (HC). (5) However, the clinical relevance of these differences is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…(2-5) Those who were less likely to seroconvert were older in age, received the BNT162b2 vaccine, and be on combination therapy with an anti-tumor necrosis factor alpha (TNF)-alpha inhibitor and an immunomodulator. (3-5)…”
Section: Introductionmentioning
confidence: 99%